2022
DOI: 10.3390/cancers14235806
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Gene Signatures to Predict the Effectiveness of Chemoimmunotherapy in Triple-Negative Breast Cancer Using Exploratory Subgroup Discovery

Abstract: Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer with limited therapeutic options. Although immunotherapy has shown potential in TNBC patients, clinical studies have only demonstrated a modest response. Therefore, the exploration of immunotherapy in combination with chemotherapy is warranted. In this project we identified immune-related gene signatures for TNBC patients that may explain differences in patients’ outcomes after anti-PD-L1+chemotherapy treatment. First, we ran the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…[ [5] , [6] , [7] , [8] , [9] , [10] , [11] ], have been applied to the medical domain. Recent studies use subgroup discovery to identify subgroups of cancer patients [ 14 , 15 ], identify predictive factors for diabetic ketoacidosis [ 16 ], or discover subgroups of patients undergoing transcatheter aortic valve implantation with high model prediction error and their distribution over the centres [ 17 ]. Gamberger et al [ 11 ] demonstrated the applicability of SGD analysis for in brain ischaemia.…”
Section: Related Workmentioning
confidence: 99%
“…[ [5] , [6] , [7] , [8] , [9] , [10] , [11] ], have been applied to the medical domain. Recent studies use subgroup discovery to identify subgroups of cancer patients [ 14 , 15 ], identify predictive factors for diabetic ketoacidosis [ 16 ], or discover subgroups of patients undergoing transcatheter aortic valve implantation with high model prediction error and their distribution over the centres [ 17 ]. Gamberger et al [ 11 ] demonstrated the applicability of SGD analysis for in brain ischaemia.…”
Section: Related Workmentioning
confidence: 99%
“…Despite such improvement, in a breast cancer scenario, triple-negative breast cancer (TNBC) remains a formidable clinical challenge due to its limited therapeutic options. Kholod O. et al [14] decode the immune-related gene signatures that hold the key to predicting chemoimmunotherapy outcomes in TNBC patients, analyzing a vast dataset encompassing 422 patients across 24 studies. Through an algorithmic approach, they categorize patients into 12 homogenous subgroups based on various parameters, including tumor mutational burden, relapse status, tumor cellularity, menopausal status, and tumor stage.…”
mentioning
confidence: 99%